PENGARUH SOCIAL MEDIA MARKETING, BRAND IMAGE DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN - I Nengah Suardhika; I Gede Rihayana; Ni Made Arie Krisnayanti (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The development of the skincare industry has made competition very tight. It takes a unique approach that companies use to compete and attract customers to use their products. The purpose of this research is to study and explain how the use of social media, brand image, and brand representation influence consumer decisions to buy Ms. skincare products. glow. A total of 85 units of respondents were selected purposively based on the criteria that they had purchased Ms. skincare products. Glow more than once. Based on multiple linear regression analysis using SPSS 23.0, this study shows that social media marketing has a positive and significant impact on consumer decisions to buy skincare products Ms. Glow in Denpasar City. In addition, the use of brand image and brand ambassadors also has a positive and significant impact on consumer decisions to buy Ms. skincare products. Glow in Denpasar City. However, the use of brand ambassadors has the greatest impact on consumers in deciding to buy Ms Glow skincare products. Keywords: social media, brand, purchase decision